PENERAPAN SETTING PROPERTI DENGAN KONSEP REALIS PADA FILM FIKSI “KAMBING HITAM” - I Ketut Agus Cahaya Sentana; I Dewa Made Darmawan; I Nyoman Payuyasa (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Directing is one of the important aspects of film production which is responsible for making creative and technical decisions from start to finish. In the context of comedy films, directing plays an important role in creating the right atmosphere and setting the right timing to produce laughter from the audience. A good director in a comedy film must also be able to manage chemistry between players and direct actors to maintain the comicality of the script that has been written. The director is also responsible for choosing the right location and set according to the concept and theme to be conveyed in the film. In the production process of this short film with the Comedy Not My Fault genre, the method of stages and procedures that have been implemented, namely SOP (Standard Operational Procedure) which includes the stages of pre-production, production, to post-production, is applied. With SOP, it makes it easier for the production team to carry out 3 aspects of production properly and correctly. In this production, the writer becomes the director who plays a very important role in the three aspects of production so that the writer and the assistant director do in-depth research at the pre-production stage to get ideas that suit production needs. To produce a successful comedy film, directors must be able to balance comedy elements and solid stories, and pay attention to what the audience wants and the right market. Thus, good directing can help create comedy films that are entertaining and captivating for the audience. In this production, the writer applies 27 scenes in this comedy short film in order to get maximum results.